Odpowiedzi

2009-11-18T15:29:58+01:00
A) (a-4)(a+5)= a² +5a -4a -20= a² +a -20
b) (7b +3)(2 -4b)= 14b -28b +6 -12b= -26b +6
c) (-3c +2d)(2c -6)= -6c² -18c +4dc -12d
d) (9s -2t)(7t -s)= 63st -9s² -14t² +2ts= 65st -9s² -14t²
e) (-10m +3n)(5n -4)= -50mn +40m +15n² -12n
f) (3kl +8k)(4 -2l)= 12kl -6kl² +32k -16kl= -4kl -6kl² +32k
g) (4xy+3)(2y +5x²y)= 8xy² +20x³y² +6y +15x²y
h) (-2p²q -3p)(5pq -3p²q²)= -10p³q² +6p4[4 jest to potęga]q³ -15p²q +9p³q²= -1p³q² +6p4[4 jest to potęga]q³ -15p²q

a) (a +3)(a-1) +(a-7)(a+5)= a² -a +3a -3 +a² +5a -7a -35= 2a² -38
b) (2b -5)(3 -2b) -(3b +2)(b -6)= (6b -4b² -15 +10b)-(3b² -18b +2b -12)= 6b -4b² -15 +10b -3b² +18b -2b +12= 32b -7b² -3
c) -7c²(5c -4) +(3c² +c)(6 -2c)= -35c³ +28c² +18c² -6c³ +6c -2c²= -41c³ +44c² +6c
d) 3m(m -4)(5m+2) -m(2m +3)(4 -3m)= 3m(5m² +2m -20m -8) -m(-8m -6m² +13 -9m)= 15m³ +6m² -60m² -24m +8m² +6m³ -13m +9m²= 21m³ -37m² -37
e) -2x(3x -5y) -(x +2y)(3x-y)= -6x² +10xy -(3x² -xy +6yx -2y²)= -6x² +10xy -3x² +xy -6yx +2y²= -9x² +5xy +2y²
2009-11-18T16:09:18+01:00
19).
a)(a-4)(a+5)=a²+5a-4a-20=a²+a-20
b)(7b+3)(2-4b)=14b-28b²+6-12b=2b-28b²+6
c)(-3c+2d)(2c-6)=-6c²+18c+14cd-12d
d)(9s-2t)(7t-s)=63st-9s²-14t²+2st=65st-9s²-14t²
e)(-10m+3n)(5n-4)=-50mn+40m+15n²-12n
f)(3kl+8k)(4-2l)=12kl-6kl²+32k-16kl=-4kl-6kl²+32k
g)(4xy+3x)(2x²y)=8xy²+20x³y²+6xy+15x³y
h)(-2p²q-3p)(5pq-3p²q²)=-10p³q²+6p⁴q³-15p²q+9p³q
20).
a)(a+3)(a-1)+(a-7)(a+5)=a²-a+3a-3+a²+5a-7a-35=2a²-38
b)(2b-5)(3+2b)-(3b+2)(b-6)=-6b-4b²-15+10b²-3b²+18b-2b+12=16b+3b²-3
c)-7c²(5c-4)+(3c²+c)(6-2c)=-35c³+28c²+18c²-6c³-6c-2c²=-41c³+44c²-6
d)3m(m-4)(5m+2)-m(2m+3)(4-3m)=3m(5m²+2m-20m-8)-m(8m-6m²+12-9m)=15m³-5m²-24+m²+6m³-12m=21m³-4m²-12m-24
e)-2x(3x-5y)-(x+2y)(3x-y)=-6x²+10xy-3x²+xy-6xy+2y²=-9x²+5xy+2y²



PROSZE:)